Serius dalam Humor : Sebuah Sudut Pandang Pendidikan Islam - Ngatoillah Linnaja; Ali Imron; Robingun Suyud El Syam (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This essay attempts to examine seriousness in humor: an Islamic educational perspective. Here the author offers a unique lens for understanding the spatiality of humor and its impact on the Islamic education process that can be used to build enjoyable learning. The type of research approach is qualitative research with a literature study method. Data sources and study analysis materials are based on scientific references through credible websites, such as Google Scholar, DOAJ, and SINTA. The results of this research show that humor is needed in something serious in order to obtain good results. This also applies to Islamic education so that a relaxed atmosphere is provided so that learning objectives can be achieved more optimally. Of course, the atmosphere that is created does not conflict with its essence, namely that humor in life should be an expression of gratitude or goodness, not exaggeration, ridicule or harming other people. This article adds to the Islamic educational literature on how to package seriousness with humor.